Farewell in corona times: To say good bye to dying next of kin in times of restrictions (Sociologisk Forskning, 2021)
In our society, great importance is attached to being able to say goodbye to loved ones when they are dying. The Covid-19 pandemic not only causes deaths but also creates barriers to being present in the dying process. In a study conducted in 2020, nine people whose next of kin died during Covid-19 restrictions were interviewed. The aim of the article is to make visible norms and ideas about final farewells and to identify how the interviewees handle their feelings when deviating from, or fulfilling, these norms. The most prominent ideals are for relatives to be physically and emotionally present at the deathbed, both to support the dying person and to better handle the grief. The interviewees who found ways to be present express pride and gratitude, while those unable to be present express anxiety, guilt, helplessness, and pain. To deal with their emotions they try to establish trust both in the necessity of the Covid-19 restrictions and in the staff that worked with their deceased relatives.
Keywords: Covid-19; restrictions; death; farewell; emotions; Corona crisis